SPECTROSCOPIC MONITORING OF NOVA VULPECULAE 2007 (V458 Vul) - Tarasova, T. N. (Одеські астрономічні публікації, 2008)
We present results of the spectroscopic monitoring of the peculiar nova V458 Vul during eleven months. At the early decline of the brightness the nova transformed from Fe II to the He/N type. The profiles of the HI and the HeI lines showed the variability connected with the rebrightening. At the final decline of the brightness the nova displays a fast variability (within a day) of the forbidden iron line profiles. The spectral features of V458 Vul allow classifying it as a hybrid "neon" nova. From the AAVSO light curve we obtained some photometric parameters, the mass of 458 Vul and the distance to the object. The nova showed a fast decline of the brightness (t2=7, t3=18 days). It reached Mν = -9.0 mag at the maximum of the brightness. The distance to the nova is in the range d=10.1-12.8 kpc. The reddening E(B-V)=0.59 towards the star is derived using the colour index of the nova at the maximum and the Balmer decrements. The white dwarf mass was derived about 1.1-1.2 M sun